Effects of Lysophosphatidylcholine on Jejuna Morphology and Its Potential Mechanism - Li, Xiaofeng; Abdel-Moneim, Abdel-Moneim Eid; Mesalam, Noura M.; Yang, Bing (Frontiers in Veterinary Science, 2022)
Lysophosphatidylcholine (LPC) plays a vital role in promoting digestion and absorption of nutrients and immunity in broilers. However, the mechanism behind LPC enhancing the jejunal digestion and absorption and broilers' immunity is unclear. Therefore, the present study was designed to reveal the important genes associated with LPC regulation in birds' jejuna. Thus, GSE94622, the gene expression microarray, was obtained from Gene Expression Omnibus (GEO). GSE94622 consists of 15 broiler jejuna samples from two LPC-treated (LPC500 and LPC1000) and the control groups. Totally 98 to 217 DEGs were identified by comparing LPC500 vs. control, LPC1000 vs. control, and LPC1000 vs. LPC500. Gene ontology (GO) analysis suggested that those DEGs were mainly involved in the one-carbon metabolic process, carbon dioxide transport, endodermal cell differentiation, the positive regulation of dipeptide transmembrane transport, cellular pH reduction, and synaptic transmission. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis indicated the DEGs were enriched in NOD-like receptor (NLR), RIG-I-like receptor (RILR), Toll-like receptor (TLR), and necroptosis signaling pathway. Moreover, many genes, such as RSAD2, OASL, EPSTI1, CMPK2, IFIH1, IFIT5, USP18, MX1, and STAT1 might be involve in promoting digestion and absorption of nutrients and immunity in broilers. In conclusion, this study enhances our understanding of LPC regulation in jejunal digestion and absorption and broilers' immunity.